Formulation and In Vitro Evaluation of Pitavastatin Oral Thin Films - Devi, Bolla Valli (International Journal of Pharmaceutical & Biological Archive, 2021)
Introduction: Among the different routes of administration, the oral route of administration continues to be the most preferred route due to various advantages including ease of administration, avoidance of pain, versatility, and most importantly patient compliance. One such relatively new dosage form is the oral strip, a thin film that is prepared using hydrophilic polymers that rapidly dissolve on the tongue or buccal cavity. Recently, fast-dissolving drug delivery systems have started gaining popularity and acceptance as new drug delivery systems, because they are easy to administer and lead to better compliance. Materials and Methods: Conventionally, these drugs have been administered as parenteral drug delivery systems, which invariably lead to poor patient compliance. This has made the pharmaceutical industry look for alternative routes of drug delivery like film drug delivery. Intraoral fast-dissolving drug delivery system is placed on the top or the floor of the tongue. It is retained at the site of application and rapidly releasesthe active agent for local and/or systemic absorption. Results: In the present study, an attempt has been made to formulate and evaluate orally disintegrating tablets films of pitavastatin by the solvent cas ting method using povidone and HPMC K4M as superdisintegrants. Conclusion: The stability studies were conducted and results suggested that the F8 formulation was stable even after 3 months of time. Based on all the above considerations, these formulas will be subjected to bioavailability studies and if it complies with all the requirement of those studies, the same formula will be commercialized.